Tinjauan Hukum Islam Terhadap Putusan Fasakh Nikah di Pengadilan Agama Surabaya Perspektif Imam Syafi’i: (Studi Kasus Putusan Pengadilan Agama Surabaya No 2516/Pdt.G/2020/PA.Sby) - Farisi, Salman Al (Muhammadiyah University of Surabaya, 2024)
This study aims to examine and analyze the fasakh decision in divorce cases decided by the Surabaya Religious Court with Number 2516/Pdt.G/2020/PA. Sby, reviewed from the perspective of Islamic law Madzhab Imam Shafi'i. The background of this research is based on the phenomenon of increasing divorce lawsuits filed by wives on the grounds of syiqāq, the absence of maintenance, and the loss of responsibility of the husband, which in Islamic law is known as the basis of fasakh. Madzhab Imam Shafi'i has an important position in providing a normative foothold for family issues in classical Islamic law. This research uses a qualitative approach with a case study type of research. The data collection technique was carried out through the study of documents on copies of court decisions, classical literature, and contemporary Islamic legal literature. Data analysis was carried out by descriptive-analytical and comparative methods between the judge's arguments in the decision and the provisions in the view of Madzhab Shafi'i. The results of the study show that the basis of the judge's consideration in the decision is in line with the principles of fasakh according to Imam Shafi'i, especially in the aspect of the husband's non-fulfillment of obligations and also the wife's apostasy. The novelty of this study lies in the effort to directly compare contemporary legal decisions with the provisions of classical fiqh, so as to show the continuity between normative Islamic law and modern judicial practices in resolving family conflicts. Keywords: Fasakh of Marriage, Imam Shafi'i, Religious Courts, Islamic Family Law.